In vitro growth pattern of rumen microbes on cellulosic feeds using buffalo and cattle rumen liquor - SANGWAN, D C; KUMAR, SHIV; SINGH, SADHANA; BHATIA, S K; DULAR, R K (The Indian Journal of Animal Sciences, 2014)
The growth pattern of anaerobes was studied by using rumen mixed culture from cattle and buffalo under in vitro rumen fermentation up to 431 hr of 9 cellulosic feeds (CP 2.1 to 20.3%, NDF 50.3 to 77.7%, ADF 38.9 to 52.3%, cellulose 26.5 to 39.7%). The competitive seprobic ability (CSA) of rumen microbes on such feed revealed relatively higher (P